Barriers and Facilitators for Female Healthcare Professionals to Be Leaders in Pakistan: A Qualitative Exploratory Study - Iftikhar S; Yasmeen R; Khan RA; Arooj M (Dove Medical Press, 2023)
Sundus Iftikhar,1 Rahila Yasmeen,2 Rehan Ahmed Khan,2 Mahwish Arooj1 1University College of Medicine and Dentistry, University of Lahore, Lahore, PB, Pakistan; 2Islamic International Medical College, Riphah International University, Rawalpindi, PB, PakistanCorrespondence: Sundus Iftikhar, 26-C extension DHA Phase 8 ex-Parkview, Lahore, Pakistan, Tel +923457363111, Email sundus@iftikhar.mePurpose: Despite being in high numbers in medical colleges, only a small proportion of women join the workforce and even fewer reach leadership positions in Pakistan. Organizations like United Nations and Women Global Health are working towards closing the gender gap. The study aims to explore the enablers and barriers for women in healthcare leadership and to explore the strategies to promote women in leadership positions in Pakistan's specific societal culture.Methods: In this qualitative exploratory study, semi-structured interviews of 16 women holding leadership positions in the health-care profession, ie, medical and dental (basic or clinical sciences) were included. The data were collected until saturation was achieved. The data were analyzed in MS Excel. Deductive and Inductive thematic analysis was done.Results: Thirty-eight codes were generated that were combined in the form of categories. The major themes that emerged from the data were: elevating factors, the shackles holding them back, let us bring them up and implicit bias. Elevating factors were intrinsic motivation and exceptional qualifications, while the shackles were related to gender bias, male insecurities, and lack of political background. It was noteworthy that differences in gender roles were highly defined by culture and religion.Conclusion: There is a need to change the perception of South Asian society and redefine gender roles through media and individual attempts. Women must take charge of their choices and believe in themselves. The institutional policies to help promote gender equality would be mentorship programs for new faculty, gender-responsive training for everyone, equal opportunities for all, and maintaining gender diversity on all committees.Keywords: gender disparity, leadership in the health profession, gender roles in Pakistani society